(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Recently, there is an increase in the incidence of myocardial infarction which manifest as a result of disrupted blood supply and oxygen to the myocardium. Objective: This study assessed the protective outcome of methanol extract of Jatropha tanjorensis leaf on liver function biomarkers and lipid profile condition in the isoprenaline induced myocardial infarction in albino rats. Methods: Thirty six (36) rats were divided at random into six (6) groups of six rats per group. Group 1 was normal control, group 2 was negative control (85mg/kg of isoprenaline only), group 3 positive control (pretreated with 2mg/kg carvedilol for 28 days), group 4 through 6 were pretreated with 200mg/kg, 400mg/kg and 600mg/kg of methanol leaves extract of Jatropha tanjorensis respectively for 28 days. Results: The extract at 200mg/kg and 400mg/kg significantly (p<0.05) decrease the AST and ALT activities, TAG and Cholesterol concentrations compared to negative control. The extract treated groups also showed significant (p<0.05) increase in the HDL concentration. The histopathological study showed marked atrophy of hepatic cord in the 600mg/kg of the extract treated group. This pointed that the extract at 600mg/kg dose could not possess hepatoprotective potency. The 400mg/kg dose extract ameliorated damage cells. Conclusion: This study revealed that 400mg/kg of the extract could serve as an agent for the prevention of hepatic cell injury and dyslipidemia.